Occupational Risk Assessment in RMG, Textile and Ship Breaking Industries of Bangladesh (Chemical Engineering Research Bulletin, 2021)
In this study occupational risk assessment in Readymade Garments (RMG), Textile and Ship Breaking Industries of Bangladesh was carried out utilizing accident database of Department of Inspection for Factories and Establishments (DIFE), Ministry of Labour and Employment. The study focused on the workplace incidents reported to DIFE from 2016-2018 in RMG, Textile and Ship Breaking industries of Bangladesh. The risk analysis was conducted based on severity and likelihood of events, the latter comprising: frequency of exposure to the hazard, duration of exposure to the hazard, probability of occurrence of a hazardous event, and technical and human possibility of avoiding or limiting the harm. To carry out the assessment, survey data including working time, accident frequency, cause of accident, nature of injury, use of personal protective equipment (PPE), health safety policy, first aid facility etc. were collected from DIFE. The risk scores and economic losses due to accidents in different years for each industry were estimated. The overall risk scores estimated for RMG and Textile industry were found to be higher than that for Ship Breaking industry. However, in Ship Breaking industry 41.3% of total incidents are of very high-risk, which is much higher than the percentage of such incidents in RMG or Textile industry. It was also found that the total compensation provided to the workers as reported to DIFE is 58.5% less of the estimated cost based on the fatality and type of injuries.Chemical Engineering Research Bulletin 21(2020) 69-76